2009
DOI: 10.1007/bf03326085
|View full text |Cite
|
Sign up to set email alerts
|

Effect of leachate loading rate and incubation period on the treatment efficiency by T. versicolor immobilized on foam cubes

Abstract: This study focuses on treatment of landfill leachate in column experiments by immobilized Trametes versicolor on polyurethane foam, collected from Nonthaburi landfill site, Thailand. In this study, glucose was used as a co-substrate. The effect of biomass growth on color removal was observed by immobilizing fungi on polyurethane foam. The same immobilized fungi were used for four cycles of 5 days each to find the reuse of fungi. Leachate was diluted to see the effect of organic loading on color removal. At opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 25 publications
3
16
0
Order By: Relevance
“…This finding is in accordance with the findings by Saetang and Babel that obtained higher COD removal compared to BOD in their study [17].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…This finding is in accordance with the findings by Saetang and Babel that obtained higher COD removal compared to BOD in their study [17].…”
Section: Discussionsupporting
confidence: 94%
“…However, COD removal occurred at most of the cycles and diluted leachate demonstrated higher COD removal after each cycles compared to raw leachate. Similar results were found by Saetang and Babel who found that removal of BOD and COD was lower when the leachate was diluted 5 times compared to concentrated leachate [17].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These enzymes are able to oxidize a variety of high-priority aromatic pollutants such as polycyclic aromatic hydrocarbons, chloromatics and polyaromatic dyes (Kotterman et al 1996). Saetang and Babel (2009) have applied immobilized T. versicolor to treat landfill leachate in column experiments since the immobilization is expected to improve the mass transfer of oxygen and nutrients for fungal mycelia by providing a large attaching surface area. Besides that, Saetang and Babel (2010) stated that the advantages of using immobilized microorganism for pollutant degradation is due to their economically cheaper, easier to handle and the immobilized fungus is reusable for several batches.…”
Section: Introductionmentioning
confidence: 99%